The participatory, modern and decentralized State in a globalized world - Aranaga Manrique, David (2007)
This article is an attempt to answer the most important question of our time: how should we participate in this globalized world, if the current primary-export growth model is only temporarily benefiting Peru due to rising international market prices? It is postulated that the State supports economic agents to face the globalization process in a competitive and efficient manner.